2017
DOI: 10.1002/micr.30209
|View full text |Cite
|
Sign up to set email alerts
|

Sequential chimeric medial femoral condyle and anterolateral thigh flow‐through flaps for one‐stage reconstructions of composite bone and soft tissue defects: Report of three cases

Abstract: Small recalcitrant non-unions with poor perfusion require reconstruction with vascularized bone flaps. Cases with concomitant large soft tissue defects are especially challenging, since vascularized soft tissue transfer is often indicated and distant microvascular anastomoses may be required. We introduce a sequential chimeric free flap composed of a medial femoral condyle corticoperiosteal flap anastomosed to an anterolateral thigh flow-through flap (MFC-ALT flap) and report its use for reconstruction of smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The radial forearm flaps were combined with ALT flaps, free jejunum segment flaps or a free osseous fibula [37]. The ALT flap itself has been described as a potential flowthrough flap for sequential connections of multiple flaps [38]. Consequently, we changed our approach in patients with free jejunum segment flaps and insufficient soft tissue of the neck towards chimeric ALT flaps that were anastomosed to internal mammary vessels outside prior operation and radiation fields, and that served as a "vascular bridge" for the jejunum, which was anastomosed to the distal ALT pedicle.…”
Section: Discussionmentioning
confidence: 99%
“…The radial forearm flaps were combined with ALT flaps, free jejunum segment flaps or a free osseous fibula [37]. The ALT flap itself has been described as a potential flowthrough flap for sequential connections of multiple flaps [38]. Consequently, we changed our approach in patients with free jejunum segment flaps and insufficient soft tissue of the neck towards chimeric ALT flaps that were anastomosed to internal mammary vessels outside prior operation and radiation fields, and that served as a "vascular bridge" for the jejunum, which was anastomosed to the distal ALT pedicle.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the donor site morbidities, sequential chimeric aps were used to repair large soft-tissue defects [16][17][18] . Qing et al reported using the bilateral chain-linked ALT perforator aps for large defects [19] .…”
Section: Discussionmentioning
confidence: 99%
“…The main drawbacks of those flaps for reconstruction of complex soft tissue defects repair motivated us to research a new method to overcome these limitations. The sequential chimeric flap consists of two or more tissue components joined together by means of a microanastomosis instead of naturally occurring (Henn et al, ; Vanmierlo, Craggs, Van Eeckhout, Zeltzer, & Hamdi, ). However, most of these combined flaps were aim to get special tissue components, such as bone or muscle, to reconstruct deep tissue structures.…”
Section: Discussionmentioning
confidence: 99%